2021
DOI: 10.1038/s41598-021-00962-8
|View full text |Cite
|
Sign up to set email alerts
|

Accurate interpretation of genetic variants in sudden unexpected death in infancy by trio-targeted gene-sequencing panel analysis

Abstract: In sudden unexpected death in infancy cases, postmortem genetic analysis with next-generation sequencing potentially can extract candidate genes associated with sudden death. However, it is difficult to accurately interpret the clinically significant genetic variants. The study aim was to conduct trio analysis of cases of sudden unexpected death in infancy and their parents to more accurately interpret the clinically significant disease-associated gene variants associated with cause of death. From the TruSight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Osawa et al showed that variations in the novel QT interval determinant NOS1AP may be involved in the occurrence of SIDS 49 . Similarly, we previously performed molecular autopsy to investigate sudden infant death 33,35,37,39,50,51 .…”
Section: Molecular Autopsy In Japanmentioning
confidence: 99%
See 2 more Smart Citations
“…Osawa et al showed that variations in the novel QT interval determinant NOS1AP may be involved in the occurrence of SIDS 49 . Similarly, we previously performed molecular autopsy to investigate sudden infant death 33,35,37,39,50,51 .…”
Section: Molecular Autopsy In Japanmentioning
confidence: 99%
“…Takahashi et al also reported a case of sudden death due to Marfan syndrome caused by an FBN1 gene variant 58 . These studies were performed using Sanger sequencing, and currently, NGS-based studies are being reported in Japan 37,39,51,[59][60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Molecular Autopsy In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies used target sequencing and exome sequencing with next-generation sequencing. However, problems arise when comprehensive exome sequencing detects many genetic variants, and the interpretation becomes difficult [5]. The mechanism at the molecular biological level is important.…”
Section: Introductionmentioning
confidence: 99%
“…NGS can detect more variations than direct sequencing and most genetic variants are classified as variants of uncertain significance (VUS) 5) , and thus multiple variations in an individual make interpretation of pathogenicity difficult. 6,7) Molecular analyses, including knock-in mouse experiments and recombinant cell experiments, as well as family pedigree analyses, are important methods for exploring this pathogenicity. However, these methods are difficult to perform during routine postmortem practice: the former is both cost-and effort-consuming, while the latter is difficult to realize, especially in sudden death cases, because there is often a lack of familial and clinical information.…”
mentioning
confidence: 99%